What drives new firms into an industry? an integrative model of entry - Barbosa, Natália (2003)
The paper focuses on the theoretical and empirical formulation of an entry model that integrates strategic considerations and firms' heterogeneity. Entry decisions are derived from a profit function, and, subsequently, the number of entrants is defined as the sum of firms that have effectively decided to enter a given industry. As the aggregation of individual entry decisions yields a discrete outcome, the econometric methodology is based on panel count data models, rendering a novel departure from previous works. The results suggest that both incumbents' behaviour towards entry and firm-specific characteristics provide additional and interesting insights in understanding entry.